2011
DOI: 10.1007/s10552-010-9722-3
|View full text |Cite
|
Sign up to set email alerts
|

Inequity in access to cancer care: a review of the Canadian literature

Abstract: Despite the policy and research attention on ensuring equitable access--equal access for equal need--to health care, research continues to identify inequities in access to cancer services. We conducted a literature review to identify the current state of knowledge about inequity in access to cancer health services in Canada in terms of the continuum of care, disease sites, and dimensions of inequity (e.g., income). We searched MEDLINE, CINAHL, and Embase for studies published between 1990 and 2009. We retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 68 publications
7
94
0
1
Order By: Relevance
“…This exacerbates current inequities in the delivery of quality health care. 19,20 The RW GPs referred more patients than their control group counterparts. This finding should be interpreted with caution due to the potential for social desirability bias, 21 and/or novelty effects.…”
Section: Discussion Summarymentioning
confidence: 99%
“…This exacerbates current inequities in the delivery of quality health care. 19,20 The RW GPs referred more patients than their control group counterparts. This finding should be interpreted with caution due to the potential for social desirability bias, 21 and/or novelty effects.…”
Section: Discussion Summarymentioning
confidence: 99%
“…A recent review of Canadian literature on inequity in access to cancer services [81] suggested that among treatments and services, evidence of inequality is most consistent and convincing in radiation therapy and end of life care. Maddison and colleagues arrive at this conclusion from an assessment of the quality of the studies conducted (primarily focusing on whether results were adjusted for need) and consideration of the level of agreement in findings.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is somewhat paradoxical. In a review of Canadian literature about access to cancer care, Maddison and colleagues [81] indicate that differences in patient selfadvocacy for care was one of two recurrent explanations offered by researchers for variations in access to cancer care in the Canadian context. That is, researchers speculated that people from advantaged group were more likely to be aware of their options, more demanding and better equipped to negotiate care.…”
Section: Conceptual Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inequities in access to cancer services along the cancer care continuum, from screening to end-of-life care, are linked to a variety of socioeconomic, geographic, and demographic factors. The research on inequity in cancer care in Canada is sparse, and the quantity of research on access to care varies by point of service, equity determinates, and disease site 27 . Barriers to access can be sorted into 4 categories: availability of services, financial barriers, nonfinancial barriers to presentation of health care needs, and barriers to equitable treatment.…”
Section: High-risk Populationsmentioning
confidence: 99%